MAKNA “BODOH” DALAM KITAB AKHBAR AL-ḤAMQA WA AL-MUGHAFALLIN KARYA IBN AL-JAUZI - Saniyyah, Sahla Nurul (Multikultura, 2026)
The term “foolish” often appears in literary works and social interactions, but it is rarely the focus of academic study. This study departs from Md. Akbar Ali Biswas's (2007) Life and Works of Ibn al-Jawzi with Special Reference to His Book Akhbar al-Hamqa wa al-Mughaffilin, which asserts that the theme of foolishness in Ibn al-Jauzi's work is universal because it can be understood across cultures and eras. However, this study has not examined its relevance to the phenomenon of modern human foolishness. Based on this gap, this study aims to reexamine the forms of stupidity in Akhbar al-Hamqa and assess its relevance to the phenomenon of modern stupidity. This study uses a qualitative literature review method with primary data in the form of the text Akhbar al-Hamqa wa al-Mughafallin and secondary data in the form of literature related to the topic. The analysis was conducted using Dietrich Bonhoeffer's Modern Stupidity theory. The results show that the forms of stupidity in the text bear substantial similarities to the phenomenon of modern stupidity, especially in interpreting stupidity as a loss of moral consciousness. Approximately 12.6% of the stories are still relevant to the modern context. This confirms that stupidity is timeless but always influenced by social and cultural contexts.